Subtitling Today : Shapes and Their Meanings. - Perego, Silvia; Bruti, Silvia (Studies in language and translation., 2015)
"Nowadays subtitling accomplishes several purposes; it is meant for diverse audiences and comes in many forms. This collection of innovative contributions explores these different manifestations, and offers a snapshot of the state of the art of a dynamic and ever-evolving field of study. This volume intentionally assembles essays that analyse subtitling in various audiovisual genres, including television series, variety programmes, operas, operettas, feature films and live conferences, and that consider various languages, such as Chinese, English, Finnish, French, Italian, Japanese and Polish. It underscores both traditional and novel viewpoints and approaches to the subject, thus broadening the horizons of such a fascinating field. The diversity of topics tackled will encourage further reflection on a well-established research area, and, as such, the volume will appeal to both novice and expert researchers and professionals."--Publisher's website.